Finance business partnering and manufacturing firms’ performance: a mediating role of non-financial performance - Zhang, Yi Fei; Namazi, Mohammad; Guo, Yong Qing; Li , Xuan (Journal of Business Economics and Management, 2020)
The effect of finance business partnering (FBP) implementation on the firm performance remains largely unexplored. The main aims of this study are to investigate whether there is a significant effect between FBP and firm performance and to identify the mediating effect of non-financial performance between FBP and firm performance. A questionnaire-based survey was conducted among 117 Chinese manufacturing firms in the year 2018, and research hypotheses were tested by partial least squares structural equation modelling (PLS-SEM). The findings showed that 1) FBP does not exert a significant and direct effect on the firms’ financial performance, 2) when non-financial measures (employees performance, internal process performance, and market performance) are used as mediating variables, the effect of all the three mediating variables on the relationship between FBP and non-financial variables are positive and significant. However, when the relationship between non-financial measures and firm’s performance is considered, the mediating effect of the non- financial variables is positive and significant only for the market performance. This study provides, for the first time, empirical evidence that non-financial performance, such as employee skills, internal processes, and market performance, can be enhanced by considering FBP. It also provides practical implications suggesting that manufacturing firms should motivate finance staff to be involved in various decision-making processes.